Social dimension of higher education: definition, indicators, models - Liubov F. Panchenko; Hennadii O. Korzhov; Andrii O. Khomiak; Vladyslav Ye. Velychko; Vladimir N. Soloviev (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the problem of strengthening the social dimension of higher education. It discusses the definition of social dimension, its indicators, models of student retention and student engagement. The article argues that students should act as active researchers of the topic of social dimension and present the ways to update the content of university courses for Sociology majors, such as "Mathematical and statistical methods of social information analysis", "Social statistics and demography", "Multivariate data analysis", "Structural equation modeling" and other courses for bachelors, master students, and PhDs in Sociology.